Comprehensive transcriptome data for endemic Schizothoracinae fish in the Tibetan Plateau - Zhou, Chaowei (Sci Data, 2020)
The Schizothoracinae fishes, endemic species in the Tibetan Plateau, are considered as ideal models for highland adaptation and speciation investigation. Despite several transcriptome studies for highland fishes have been reported before, the transcriptome information of Schizothoracinae is still lacking. To obtain comprehensive transcriptome data for Schizothoracinae, the transcriptome of a total of 183 samples from 14 representative Schizothoracinae species, were sequenced and de novo assembled. As a result, about 1,363 Gb transcriptome clean data was obtained. After the assembly, we obtain 76,602–154,860 unigenes for each species with sequence N50 length of 1,564–2,143 bp. More than half of the unigenes were functionally annotated by public databases. The Schizothoracinae fishes in this work exhibited diversified ecological distributions, phenotype characters and feeding habits; therefore, the comprehensive transcriptome data of those species provided valuable information for the environmental adaptation and speciation of Schizothoracinae in the Tibetan Plateau.